Assessing the Influence of Practical Training on Perceived Employability Among Public University Students in Malaysia - Rosmelisa Yusof; Siby James; Jia Qi Ng; Naazhim Bin Roslan; Shu Luan Ng; Niwasini A/P Sathiaselan; Sharim Qureshi; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2024)
This study examines the influence of practical training on the perceived employability of students from public universities in Malaysia. As employability becomes an important aspect of higher education, practical training is often viewed as essential in preparing students for the workforce. This study assesses the impact of practical training on students' perceived employability by evaluating the quality, effectiveness, and satisfaction associated with such training, all of which are important for career readiness and success. Quantitative data was collected through a survey questionnaire distributed via Google Forms. The findings highlight the positive impacts of practical training on students' perceived employability, including skill development, increased confidence, and improved employer perception. Also, the study identifies areas for enhancing training programs to better prepare students for the workforce. The insights gained aim to inform improvements in university career readiness programs and highlight the importance of practical training in enhancing students' employability.